2019
DOI: 10.22434/ifamr2018.0004
|View full text |Cite
|
Sign up to set email alerts
|

Management of socioenvironmental factors of reputational risk in the beef supply chain in the Brazilian Amazon region

Abstract: Increased production of Brazilian beef has been associated with negative impacts in the Amazon region. Supply chain interventions are increasingly common to avoid social and environmental consequences in the area, but evidence about how companies have managed these efforts is scarce. The present study identified the main sources of reputational risks in Brazilian Amazon beef supply chains and the actions taken by slaughterhouses to manage these types of risk. A multiple case study was developed in Brazilian be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Thereby, companies in the food sector in Brazil prioritize economic issues of sustainable use to select suppliers, and have a growing interest in environmental criteria as these result in market value. However, social and ethical issues, as important as the others, still have little importance and visibility in this sector (Galuchi et al, 2019;Freitas et al, 2020;Pereira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, companies in the food sector in Brazil prioritize economic issues of sustainable use to select suppliers, and have a growing interest in environmental criteria as these result in market value. However, social and ethical issues, as important as the others, still have little importance and visibility in this sector (Galuchi et al, 2019;Freitas et al, 2020;Pereira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Rajesh reveals the driving forces behind the management of social and environmental risk management (SERM) within resilient supply chains, emphasizing their pivotal role in encouraging enterprises to adopt SERM practices [8]. Galuchi et al investigate the primary origins of reputational risks in the beef supply chains of the Brazilian Amazon, along with the strategies implemented by slaughterhouses to address such risks [46].…”
Section: Sustainable Social Risk Management Of Supply Chainmentioning
confidence: 99%
“…Within this research stream, the extent of disclosed information has been shown to positively influence corporate image (Plotnick, 2010) and the mutual recognition and resolution of normative conflicts (Palazzo and Scherer, 2006;Scherer and Palazzo, 2007). In turn, the general public's perceptions of a firm's reputation and responses to societal expectations have been shown to noticeably (although in part indirectly) affect future shareholder value (Galuchi et al, 2019;Raithel and Schwaiger, 2015;Rindova et al, 2010;Roberts and Dowling, 2002). With consumers, employees and investors being increasingly interested in the social and environmental performance of companies, corporate reputation represents a unique and valuable resource.…”
Section: ■ Resource-based Motives For Csr Disclosurementioning
confidence: 99%